Rural Finance Policies 2 - Impact of microfinance on poverty alleviation: what does emerging evidence indicate? - Sharma, Manohar (International Food Policy Research Institute, 2000)
The spectacular growth of the microfinance industry has been fueled not by market forces but by conscious actions of national governments, nongovernmental organizations (NGOs), and donors who view microfinance as an effective tool for alleviating poverty. Since much of the impetus behind this large and increasing support for microfinance hinges on the assumption that its economic and social impacts are significant, it needs to be examined more closely. This review... indicates that impact studies themselves must be improved to make more accurate assessments of benefits. This is important, for only through cycles of innovation, experimentation, and evaluation can we hope to establish lasting institutions that alleviate the financial constraints faced by the poor.